Application of capacitive coupling to the design of an absolute-coordinate pointing device - Eng, Chong Tan; IEEE, Senior Member; Abdul Rahman, Abdul Wahab; Kay , Min Low (IEEE, 2005)
Capacitive coupling is applied to develop an absolutecoordinate-based interface system for a personal computer (PC). The system consists of a pointing device and a digitizing tablet. The pointing device is a cordless stylus that does not need any power supply. The digitizing tablet is wire-connected to the PC via a serial or universal-serial-bus (USB) port. The technique of capacitive coupling is used to detect both the x and y positions of the tablet and also if any of the stylus buttons is pressed. Measured voltage values and analyses of capacitive coupling signals are given. Experimental results show that the interface system is reliable, and its performance is robust.